Combination therapy in early rheumatoid arthritis: a randomised, controlled, double blind 52 week clinical trial of sulphasalazine and methotrexate compared with the single components. Issue 4 (1st April 1999) - Dougados, Maxime; Combe, Bernard; Cantagrel, Alain; Goupille, Philippe; Olive, Patrick; Schattenkirchner, Manfred; Meusser, S; Paimela, L; Rau, Rolf; Zeidler, Henning; Leirisalo-Repo, Marjatta; Peldan, Kristiina
Abstract : OBJECTIVES: To investigate the potential clinical benefit of a combination therapy. METHODS: 205 patients fulfilling the ACR criteria for rheumatoid arthritis (RA), not treated with disease modifying anti-rheumatoid drugs previously, with an early (⩽1 year duration), active (Disease Activity Score (DAS) > 3.0), rheumatoid factor and/or HLA DR 1/4 positive disease were randomised between sulphasalazine (SASP) 2000 (maximum 3000) mg daily (n = 68), or methotrexate (MTX) 7.5 (maximum 15) mg weekly (n = 69) or the combination (SASP + MTX) of both (n = 68). RESULTS: The mean changes in the DAS during the one year follow up of the study was −1.15, −0.87, −1.26 in the SASP, MTX, and SASP + MTX group respectively (p = 0.019). However, there was no statistically significant difference in terms of either EULAR good responders 34%, 38%, 38% or ACR criteria responders 59%, 59%, 65% in the SASP, MTX, and SASP + MTX group respectively. Radiological progression evaluated by the modified Sharp score was very modest in the three groups: mean changes in erosion score: +2.4, +2.4, +1.9, in narrowing score: +2.3, +2.1, +1.6 and in total damage score: +4.6, +4.5, +3.5, in the SASP, MTX, and SASP + MTX groups respectively. Adverse events occurred more frequently in the SASP + MTX group 91% versus 75% in the SASP and MTX group (p = 0.025). Nausea was the most frequent side effect: 32%, 23%, 49% in the SASP, MTX, and SASP + MTX groups respectively (p = 0.007). CONCLUSION: This study suggests that an early initiation therapy of disease modifying drug seems to be of benefit. However, this study was unable to demonstrate a clinically relevant superiority of the combination therapy although several outcomes were in favour of this observation. The tolerability of the three treatment modalities seems acceptable.